Rekognisi Moderasi Beragama Melalui Deklarasi Tiga Dosa Besar Pendidikan di SMP Pelita Al-Qur’an Wonosobo - Robingun Suyud El Syam; M. Yusuf. AN (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
All forms of violence and crime, including intolerance, bullying and sexual violence, are not appropriate in an educational setting. So it is necessary to take concrete steps from the school to eradicate these three behaviors from the educational environment. Through a phenomenological approach to the declaration of the three grave sins of education, the results of the study reveal: that religious moderation can be a solution to overcoming the three great sins of education: intolerance, bullying, and sexual violence. By making religious moderation an educational strategy in schools, these three grave sins can be prevented and removed from the educational environment. This research contributes to the development of the school curriculum, especially the cognitive development of adolescents as well as the prevention and treatment that must be carried out.